Assessing Current Therapeutic Approaches to Decode Potential Resistance Mechanisms in Glioblastomas - Sze, Chun-I; Chiang, Ming-Fu; Su, Wan-Pei; Chen, Yu-An; Chang, Nan-Shan (Frontiers in Oncology, 2013)
Unique astrocytic cell infiltrating growth and glial tumor growth in the confined skull make human glioblastoma multiforme (GBM) one of the most difficult cancers to treat in modern medicine. Prognosis for patients is very poor, as they die more or less within 12 months. Patients either die of the cancer itself, or secondary complications such as cerebral edema, herniations, or hemorrhages. GBMs rarely metastasize to other organs. However, GBM recurrence associated with resistance to therapeutic drugs is common. Patients die shortly after relapse. GBM is indeed an outstanding cancer model to search for potential mechanisms for drug resistance. Here, we reviewed the current cancer biology of gliomas and their pathophysiological events that contribute to the development of therapeutic resistance. We have addressed the potential roles of cancer stem cells, epigenetic modifications, and epithelial mesenchymal transition (EMT) in the development of resistance to temozolomide (TMZ) and other drugs in GBMs. The potential role of TIAF1 (TGF-β-induced antiapoptotic factor) overexpression and generation of intratumor amyloid fibrils for conferring drug resistance in GBMs is discussed.